Implementation of an Oxytocin Checklist to Improve Clinical Outcomes. Issue 3 (May 2018) - Sundin, Courtney; Mazac, Lauren; Ellis, Kathleen; Garbo, Candon
Abstract: Background: Oxytocin is one of the most common drugs administered in obstetrics. Since its designation as a high-alert medication by the Institute for Safe Medication Practices in 2007, there has been much attention to oxytocin administration during labor. Oxytocin is generally safe when administered correctly, but adverse perinatal outcomes can occur during uterine tachysystole. Purpose: The purpose of this project was to evaluate and compare results of maternal and fetal outcomes of induction of labor for women at term prior to and after implementation of a newly developed oxytocin checklist. Project Design and Methods: To evaluate the practice change associated with the implementation of the new oxytocin checklist, 200 cases based on retrospective medical record reviews were compared with 200 cases after implementation. Results: Use of the checklist was associated with several significant clinical outcomes, including decreases in tachysystole, decreases in cesarean births for concern about fetal status based on electronic fetal monitoring data, decreases in length of first stage labor, and decreases in maximum dose of oxytocin. Clinical Implications: Results are similar to previous research. Early physician buy-in, clinical team education, and ongoing evaluation enhanced facilitation of the oxytocin checklist. Clinical outcomes were favorable. Abstract : Oxytocin checklists can be helpful in standardizing clinical practice during induction and augmentation of labor. In this quality improvement project, the authors found use of the checklist was favorably received by the labor nurses and was associated with several positive clinical outcomes such as a lower cesarean birth rate, a shorter first stage labor, less tachysystole, less overall dose of oxytocin, and less need to titrate the dose based on uterine or fetal status.